Trombocyty jako ukazatel aktivity u Crohnovy nemoci lécené úplnou parenterální a/nebo enterální výzivou - Bures, J; Horácek, J; Pecka, M; Tichý, M; Cervenka, B; Král, B; Fixa, B; Komárková, O; Pidrman, V (Vnitrni lekarstvi, 1994)
UNLABELLED: Inflammatory bowel disease can be associated with increased platelet count. Aim of our study was focused on assessing thrombocyte count in evaluation of the activity in Crohn's disease (CD). The study included a total of 19 patients [6 men, 13 women (aged 18-57 years, mean 33, median 28]. All patients were malnourished in active stage of the disease on total parenteral and/or enteral nutrition (TP/EN). Thrombocytes were estimated at the beginning and after 3 weeks of TP/EN in venous blood sample using automatic analyser Coulter Counter JT3 (normal range: 130-380.10(9)/l). Serum prealbumin, transferrin, haptoglobin, alpha 1-orosomucoid and C-reactive protein were measured simultaneously. Thrombocytes count below 400.10(9)/l was found only in 1/19 at the beginning and in 7/19 patients in the end of the study. After 3 weeks of TP/EN a significant platelet count fall was found (mean +/- sd: 472 +/- 98 vs. 354 +/- 110, p < 0.01). A correlation was found between thrombocytes and serum prealbumin (r = -0.3871, p < 0.05), haptoglobin (r = 0.5247, p < 0.001), alpha 1-orosomucoid (r = 0.4857, p < 0.01) a C-reactive protein (r = 0.4354, p < 0.01). CONCLUSION: Thrombocyte count helped in the assessing of disease activity in CD on 3-week-TP/EN. Improvement of clinical status, increase of nutritional parameters and decrease of positive acute phase reactants were associated with a fall of platelet count in 15/19 patients.
Keywords: parenterální výživa úplná; Humans; lidé středního věku; Female; dospělí; Crohn Disease; lidé; Adult; ženské pohlaví; Male; Middle Aged; Adolescent; Crohnova nemoc; Enteral Nutrition; Platelet Count; počet trombocytů; enterální výživa; mužské pohlaví; Parenteral Nutrition, Total; mladiství